Implementasi Model Problem Based Learning pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 13 Pulau Rimau - Noni Juli Astuti; Saipul Annur; Asri Karolina (Pusat Riset dan Inovasi Nasional, 2025)
This study explores the implementation of the Problem-Based Learning (PBL) model in Islamic Religious Education at Elementary School 13 Pulau Rimau, including its supporting and inhibiting factors. Using a qualitative descriptive case study, data were collected through observation, interviews, and documentation involving teachers and students. The study found that effective implementation of PBL requires thorough planning involving syllabus, lesson plans, objectives, methods, media, and resources. The learning process follows five main PBL stages and assesses students' attitudes, knowledge, and skills. The research recommends teachers to improve and develop their use of PBL to enhance student-centered learning and ensure more meaningful educational experiences.